2017
DOI: 10.1007/s10344-017-1120-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of box-traps for wild roe deer: behaviour, injuries and recaptures

Abstract: Tracking devices are commonly used to locate and monitor wild animals for studying spatial ecology and survival rates. There is growing interest in capture effects, partially to minimize the impact on the study species, but also for animal welfare reasons. This study aims to examine roe deer behaviour in box-traps, when restrained, when released and during recaptures to quantify injuries and deaths over a period of 41 years. We use data from 2911 captures from 926 individuals between 1973 and 2014. We recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Refinement (Table 3) includes, for example, the use anesthesia, tranquilization and light-weight radiotransmitters (Harcourt et al 2010, McGuire et al 2014. For minimum injuries and capture of non-target species, it has been recommended to use call playback and taxidermy decoys (Veltheim et al 2015), and to use traps that have been shown to cause no or minimal injuries, for instance, replacing foothold traps with box traps (Kolbe et al 2003, Bergvall et al 2017).…”
Section: Application Of the 3rs Into Wildlife Researchmentioning
confidence: 99%
“…Refinement (Table 3) includes, for example, the use anesthesia, tranquilization and light-weight radiotransmitters (Harcourt et al 2010, McGuire et al 2014. For minimum injuries and capture of non-target species, it has been recommended to use call playback and taxidermy decoys (Veltheim et al 2015), and to use traps that have been shown to cause no or minimal injuries, for instance, replacing foothold traps with box traps (Kolbe et al 2003, Bergvall et al 2017).…”
Section: Application Of the 3rs Into Wildlife Researchmentioning
confidence: 99%
“…Abeyesinghe et al 1997, Carragher et al 1997, to specific situations (e.g. DeNicola and Swihart 1997) as live captures in traps (Bergvall et al 2017) or chemical immobilisation (e.g. Sandegren et al 1987, Arnemo 1995, Mentaberre et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…A novel object, such as the box trap is likely to initially induce fear [ 17 ] and a neophobic stress response (see [ 53 ] for an experimental approach on roe deer). Subsequently, however, when food is offered in proximity to and inside the boxes, habituation and counter conditioning should occur, so that the box will become a positive stimulus associated with food [ 41 ]. Hence, despite the stressful event of capture and release, may still be associated with a reward that encourages the animal to re-visit the area with the box trap independent from their willingness to re-enter the trap.…”
Section: Discussionmentioning
confidence: 99%
“…We monitored 198 total capture events with two different box trap methods: “box trap (174 captures from seven populations), where the traps were checked several hours after capture (typically in the morning, if traps were set in the evening; [ 40 , 41 ]; “box trap short” (24 captures from two populations), when the traps were checked a maximum of two hours after capture that was notified to operators via remote communication [ 42 ].…”
Section: Methodsmentioning
confidence: 99%